DYNAMICS OF DA’WAH COMMUNICATION IN THE MINORITY OF TORAJA MUSLIM - Qaharuddin Tahir; Sattu Alang; Nurhidayat Muhammad Said; Abd. Halik (Universitas Islam Negeri Alauddin Makassar, 2020)
This study discusses the dynamics of da'wah communication that occurs in the Muslim minority area of Tana Toraja. The main problem discussed was how the dynamics of da'wah communication in the Muslim minority area of Tana Toraja. This research is a qualitative research, with a phenomenological approach in the context of da'wah and communication. Data collection was carried out by observation, interviews, and literature review. The data analysis technique was carried out, referring to the data analysis principles put forward by Miles and Huberman. It offers an interactive model analysis system, which consists of three components, namely data reduction, data display, and drawing conclusions. The research suggested that the dynamics of da'wah communication in the Muslim minority areas of Toraja experienced five phases with different dynamics, namely the pre-colonial era, the colonial era, the independence era, the New Order era, and the reform era.